The Bioarchaeology of Migration in the Ancient Mediterranean. (25th February 2021) - Leppard, Thomas P.; Esposito, Carmen; Esposito, Massimiliano
Abstract : The Mediterranean is often regarded as characterized by high levels of human mobility and migration, which are in turn considered to have driven large-scale cultural effects. However, this supposition is problematic, in that it relies on various types of proxy for human movement, rather than on direct bioarchaeological evidence. Accordingly, in this study we attempt to quantify diachronic Mediterranean mobility and migration by undertaking the first meta-analysis of the burgeoning radiogenic isotope datasets now available from the Mediterranean. We gathered 87Sr/ 86Sr data derived from funerary populations from the Neolithic to the late Roman period. We imposed a data-hygiene regime, discarding low-quality, methodologically idiosyncratic, or other potentially erroneous data; this resulted in a cleansed and trimmed dataset (n = 899). Within this dataset, we find that mean rates of post-juvenile migration are relatively low. Utilizing the methodologies specific to individual studies, the mean nonlocal rate is 9.57%. Imposing a standard methodology on the most statistically robust data (resulting in n = 702) allows us to recompute a mean nonlocal rate of 5.84%. In both the data as originally reported and as recomputed, we detect comparatively higher levels of migration in the period 7000–3500 BC, followed by decreasing levels of migration in the later Holocene. We discuss the implications of these results for how we understand longterm cultural and behavioral change in the Mediterranean.